A high-strength and high-plasticity CrCoNi-based multi-principal alloy and preparation method thereof

By introducing L12 nanometer precipitation phase structure into the CrCoNi matrix and using multi-pass cold rolling and recrystallization annealing, the problem of toughness mismatch between CrCoNi-based multi-main alloys is solved, and the coordinated matching between high strength and high plasticity is achieved.

CN116287929BActive Publication Date: 2025-03-14ZHEJIANG UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202310277759.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-21
Publication Date
2025-03-14
Estimated Expiration
2043-03-21

AI Technical Summary

Technical Problem

While increasing the strength, existing CrCoNi-based multi-main alloys usually lead to a decrease in plasticity, making it difficult to have both high strength and high plasticity.

Method used

By adding a small amount of L12 nano-precipitation phase structure (Ni,Co)3 (Al,Ti) to the CrCoNi matrix, using multi-pass cold rolling process and recrystallization annealing treatment, combined with isothermal aging heat treatment, a high-strength and high-plastic L12 co-precipitation strengthened CrCoNi-based multi-main alloy was prepared.

Benefits of technology

The coordinated matching of high strength and high plasticity of CrCoNi-based multi-main alloy was achieved, the room temperature tensile yield strength reached 1006MPa, the ultimate tensile strength reached 1460MPa, and the elongation of fracture was 40.5%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116287929B_ABST
    Figure CN116287929B_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength and high-plasticity L12 coherent nano-precipitation strengthened CrCoNi-based multi-principal alloy, the element composition is (CrCoNi) in atomic ratio 100‑a‑b Al a Ti b , wherein Cr, Co, and Ni have an equal atomic ratio, 4.5≤a≤5.5, 4.5≤b≤5.5. The CrCoNi-based multi-principal alloy of the present invention contains a high-density L12 coherent nano-precipitated phase structure (Ni, Co)3(Al, Ti), and the preparation method comprises: 100‑a‑b Al a Ti b The required amount of metal single substance raw materials is weighed and smelted, and the obtained original ingot of the multi-principal alloy is subjected to a solid solution homogenization annealing treatment at 1100-1300°C for 1-4h; the multi-principal alloy after the solid solution homogenization annealing treatment is rolled by a multi-pass cold rolling process, with a total thinning amount of 80%-85%; the rolled multi-principal alloy is subjected to a recrystallization annealing treatment at 1100-1300°C for 1-30min; the multi-principal alloy after the recrystallization annealing is subjected to an isothermal aging heat treatment at 600-650°C for 1-3h.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high-performance multi-principal-component alloys, and in particular to a high-strength and high-plasticity L12 coherent nano-precipitation strengthened CrCoNi-based multi-principal-component alloy and a preparation method thereof. Background Art

[0002] As an advanced structural metal material, multi-principal alloy has good application prospects in the fields of national defense, military industry, aerospace, etc. due to its excellent high strength, ductility, fracture toughness, wear resistance and corrosion resistance, and has been widely studied in recent years.

[0003] The mechanical properties of metal structural materials directly determine the stability of the device structure and service performance. Strength and ductility are the two most basic and important mechanical properties of metal structural materials. How to break the inverted relationship between the two and achieve the coordination of strength and plasticity of the material is an eternal theme in the research of metal structural materials.

[0004] Single-phase CrCoNi medium entropy alloys with FCC structure usually have high tensile ductility and excellent toughness, but their room temperature strength is usually very low. Second phase strengthening is considered to be an effective strategy to significantly improve the strength of materials. A large number of works, including composite materials, use this strategy, but improving strength through this strategy usually comes at the expense of plasticity. The main reason for this strong-plastic mutual exclusion is that the introduction of the second phase, which has a huge difference in interface matching with the matrix, causes non-uniform plastic deformation, causing excessive accumulation of dislocations at the interface between the two phases, thereby causing local stress concentration, causing cracks to initiate prematurely at the interface between the reinforcement phase and the matrix, and then causing plastic instability.

[0005] The patent specification with the publication number CN 112853237 A discloses a high yield strength CoCrNi-based medium entropy alloy, and its preparation method includes selecting (CoCrNi)Al3Ti3 medium entropy alloy ingots, hot rolling, homogenization annealing, hot rolling, cold rolling (total deformation 60%), 900℃ recrystallization annealing for 1-2h, 600℃ 8-9h aging insulation and other processes. The (CoCrNi)Al3Ti3 medium entropy alloy prepared by the patented technical method has a fracture elongation of less than 35%. Although the tensile yield strength and ultimate tensile strength of more than 1000MPa can be achieved, the fracture elongation will be significantly reduced (less than 20%). If the fracture elongation of more than 30% is to be achieved, the tensile yield strength cannot reach 1000MPa.

[0006] The patent specification with publication number CN 115233077 A discloses a high aluminum and high titanium content nano-coherent precipitation strengthened CoCrNi based medium entropy alloy, the composition is Co 37 Cr 14 Ni37 Al6Ti6 contains a high-density nano-coherent precipitation structure (Ni, Co, Cr) 3 (Al, Ti), and the nano-coherent precipitation phase (Ni, Co, Cr) 3 (Al, Ti) exists in the form of L12 phase. The preparation method includes homogenizing heat treatment, rolling (thickness reduction 40%-70%), 1000-1050℃1.5-60min recrystallization heat treatment and aging heat treatment of the suction cast medium entropy alloy sheet. Co 37 Cr 14 Ni 37 Although the Al6Ti6 alloy can achieve an elongation at break of more than 40%, the corresponding tensile yield strength cannot reach 1000 MPa, and the ultimate tensile strength cannot reach 1400 MPa.

[0007] Therefore, developing coherent nano-precipitation strengthened multi-principal component alloys with both high strength and high plasticity is an important scientific problem that needs to be urgently solved in the field of structural multi-principal component alloys. Summary of the invention

[0008] In response to the above-mentioned technical problems and deficiencies in the art, the present invention provides a high-strength and high-plasticity L12 coherent nano-precipitation strengthened CrCoNi-based multi-principal component alloy and a preparation method thereof, which solves the problems of mismatch and incoordination in strength and toughness of CrCoNi-based multi-principal component alloys in the current prior art.

[0009] The specific technical solutions are as follows:

[0010] A high-strength and high-plasticity L12 coherent nano-precipitation strengthened CrCoNi-based multi-principal alloy, wherein the element composition of the high-strength and high-plasticity L12 coherent nano-precipitation strengthened CrCoNi-based multi-principal alloy is (CrCoNi) in atomic ratio. 100-a-b Al a Ti b , where Cr, Co and Ni have equal atomic ratios, 4.5≤a≤5.5, 4.5≤b≤5.5.

[0011] The high-strength and high-plasticity L12 coherent nano-precipitation strengthened CrCoNi-based multi-principal alloy contains a high-density L12 coherent nano-precipitation phase structure (Ni, Co) 3 (Al, Ti), and the preparation method thereof comprises:

[0012] Step 1: By atomic ratio (CrCoNi) 100-a-b Al a Ti b , wherein Cr, Co and Ni have equal atomic ratios, 4.5≤a≤5.5, 4.5≤b≤5.5, weigh the required amount of metal single substance raw materials for smelting to obtain a multi-principal alloy original ingot;

[0013] Step 2: After smelting, the original ingot of the multi-principal alloy is subjected to solid solution homogenization annealing treatment at a temperature of 1100-1300° C. and a holding time of 1-4 h;

[0014] Step 3, rolling the multi-principal alloy after solution homogenization annealing by a multi-pass cold rolling process, with a total thinning amount of 80%-85%, which is conducive to alloy grain refinement, so that the final alloy has both high strength and high plasticity;

[0015] Step 4, subjecting the rolled multi-principal alloy to recrystallization annealing treatment, the annealing temperature is 1100-1300° C., the holding time is 1-30 min, preferably 1-2 min; the recrystallization annealing treatment will affect the residual stress of the alloy, and a lower annealing temperature and a longer annealing time will easily lead to the growth of alloy grains, thereby making it difficult for the final alloy to have both high strength and high plasticity;

[0016] Step 5: subjecting the multi-principal alloy after recrystallization annealing to isothermal aging heat treatment, with the annealing temperature being 600-650° C. and the holding time being 1-3 h.

[0017] In a preferred embodiment, the element composition of the high-strength and high-plasticity L12 coherent nano-precipitation strengthened CrCoNi-based multi-principal alloy is (CrCoNi) in atomic ratio: 90 Al5Ti5, that is, a=b=5.

[0018] Preferably, in step 1, the mass purity of the metal element raw material is greater than or equal to 99.95%.

[0019] Preferably, in step 1, the metal raw material is polished to remove surface oxide scale before smelting.

[0020] Preferably, in step 1, the smelting specifically comprises: placing the metal element raw material into a vacuum arc melting furnace for smelting under an argon protective atmosphere, wherein the smelting current is maintained at 400-500A, electromagnetic stirring is added during the smelting process, and the smelting is repeated 4-6 times.

[0021] Preferably, after the solid solution homogenization annealing treatment, the recrystallization annealing treatment and the isothermal aging heat treatment, the multi-principal component alloy is cooled to room temperature by water quenching.

[0022] A most preferred method for preparing a high-strength and high-plasticity L12 coherent nano-precipitation strengthened CrCoNi-based multi-principal alloy comprises:

[0023] Step 1: By atomic ratio (CrCoNi) 90Al5Ti5, wherein Cr, Co and Ni have equal atomic ratios, and the required amount of metal single substance raw materials are weighed and smelted to obtain a multi-principal alloy original ingot;

[0024] Step 2: After smelting, the original ingot of the multi-principal alloy is subjected to solid solution homogenization annealing treatment at a temperature of 1100° C. and a holding time of 3 h;

[0025] Step 3, rolling the multi-principal alloy after solid solution homogenization annealing treatment by a multi-pass cold rolling process, with a total thinning amount of 85%;

[0026] Step 4, performing recrystallization annealing treatment on the rolled multi-principal alloy, the annealing temperature is 1100° C., and the holding time is 1.5 min;

[0027] Step 5: subjecting the multi-principal alloy after recrystallization annealing to isothermal aging heat treatment, with the annealing temperature being 600° C. and the holding time being 2 h.

[0028] The high-strength and high-plasticity L12 coherent nano-precipitation strengthened CrCoNi-based multi-principal element alloy obtained has a room temperature tensile yield strength of 1006MPa, a room temperature ultimate tensile strength of 1460MPa, and a fracture elongation of 40.5%, and has excellent strength-plasticity matching at room temperature.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention obtains an L12 coherent nano-precipitation-strengthened CrCoNi-based multi-principal alloy by adding a small amount of L12 nano-precipitation phase-forming elements Al and Ti to a CrCoNi multi-principal matrix alloy with equal molar ratios of Cr, Co, and Ni. Compared with the currently available FCC system multi-principal alloy, the L12 coherent nano-precipitation-strengthened CrCoNi-based multi-principal alloy obtained by the present invention has better strength-plasticity matching, and the preparation method of the high-strength and high-plasticity L12 coherent nano-precipitation-strengthened CrCoNi-based multi-principal alloy proposed by the present invention is easy to operate and has potential advantages for mass production of multi-principal alloys with excellent mechanical properties and engineering application promotion.

[0031] The alloy prepared by the present invention can meet the application scenarios of most structural materials, and the present invention also has great engineering application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the X-ray diffraction pattern of the CrCoNi-based multi-principal alloy prepared in Example 1.

[0033] Figure 2High-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) characterization and atomic-level EDS mapping (EDS-mapping) of the interface precipitation phase of the CrCoNi-based multi-principal alloy prepared in Example 1 with atomic-level resolution.

[0034] Figure 3 This is the room temperature quasi-static tensile engineering stress-engineering strain curve of the CrCoNi-based multi-principal element alloy prepared in Example 1.

[0035] Figure 4 This is the room temperature quasi-static tensile engineering stress-engineering strain curve of the CrCoNi-based multi-principal element alloy prepared in Comparative Example 1.

[0036] Figure 5 This is a scanning electron microscope (SEM) photograph of the CrCoNi-based multi-principal component alloy prepared in Comparative Example 2. DETAILED DESCRIPTION

[0037] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0038] The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers.

[0039] Example 1

[0040] A method for preparing a high-strength and high-plasticity L12 coherent nano-precipitation strengthened CrCoNi-based multi-principal alloy specifically comprises the following steps:

[0041] Step 1: Grind and remove the surface oxide scale of Cr, Co, Ni, Al, and Ti metal raw materials, and the mass purity of the metal raw materials must be greater than or equal to 99.95%;

[0042] Step 2, weighing 30at% Cr, 30at% Co, 30at% Ni, 5at% Al, and 5at% Ti;

[0043] Step 3, placing the metal single substance raw material weighed in step 2 into a vacuum arc melting furnace for melting under a high-purity argon protection atmosphere; wherein the melting current is maintained at 450A, electromagnetic stirring is added during the melting process, and the melting is repeated 5 times to obtain a multi-principal alloy original ingot;

[0044] Step 4: After smelting, solid solution homogenization annealing treatment is performed at a temperature of 1100°C and a holding time of 3 hours;

[0045] Step 5, rolling the multi-principal alloy after solution treatment by a multi-pass cold rolling process, with a total thinning amount of 85%;

[0046] Step 6: Perform recrystallization annealing on the rolled multi-principal alloy at a temperature of 1100° C. and a holding time of 1.5 min;

[0047] Step 7, subjecting the multi-principal alloy after recrystallization annealing to isothermal aging heat treatment, with the annealing temperature being 600° C. and the holding time being 2 h;

[0048] It should be noted that after the solid solution homogenization annealing treatment, the recrystallization annealing treatment and the isothermal aging heat treatment, the multi-principal alloy is cooled to room temperature by water quenching.

[0049] In order to determine the phase composition of the multi-principal alloy prepared in this embodiment, an X-ray diffraction test was performed on the multi-principal alloy prepared in this embodiment, and the obtained test spectrum is as follows: Figure 1 As shown, only the characteristic peaks of FCC structure are seen in the spectrum, and no diffraction peaks of other phases are seen.

[0050] In order to test whether the multi-principal alloy prepared in this example precipitates fine harmful phases at the interface that are difficult to characterize by XRD, such as Sigma phase and Hesluer phase, the structure at the interface was characterized by atomic-level resolution high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) and atomic-level EDS-mapping. The results are shown in Figure 2. Figure 2 As shown in the figure, it can be seen that the interface precipitation phase is the chromium-poor L12 ordered phase (Ni, Co) 3 (Al, Ti) and the chromium-rich BCC phase.

[0051] In order to determine the room temperature mechanical properties of the multi-principal alloy prepared in this embodiment, a room temperature quasi-static tensile test was performed on the multi-principal alloy prepared in this embodiment. The obtained tensile engineering stress-engineering strain curve is shown in FIG. Figure 3 As shown in the figure, it can be seen that the room temperature tensile yield strength of the multi-principal component alloy prepared in this embodiment is 1006MPa, the room temperature ultimate tensile strength is 1460MPa, and the elongation at break is 40.5%. It can be concluded that the multi-principal component alloy prepared in this embodiment has excellent strength-plasticity matching at room temperature.

[0052] Comparative Example 1

[0053] A method for preparing a CrCoNi-based multi-principal alloy specifically comprises the following steps:

[0054] Step 1: Grind and remove the surface oxide scale of Cr, Co, Ni, Al, and Ti metal raw materials, and the mass purity of the metal raw materials must be greater than or equal to 99.95%;

[0055] Step 2, weighing 30at% Cr, 30at% Co, 30at% Ni, 5at% Al, and 5at% Ti;

[0056] Step 3, placing the metal single substance raw material weighed in step 2 into a vacuum arc melting furnace for melting under a high-purity argon protection atmosphere; wherein the melting current is maintained at 450A, electromagnetic stirring is added during the melting process, and the melting is repeated 5 times to obtain a multi-principal alloy original ingot;

[0057] Step 4: After smelting, solid solution homogenization annealing treatment is performed at a temperature of 1100°C and a holding time of 3 hours;

[0058] Step 5, rolling the multi-principal alloy after solution treatment by a multi-pass cold rolling process, with a total thinning amount of 85%;

[0059] Step 6: Perform recrystallization annealing on the rolled multi-principal alloy at a temperature of 1100° C. and a holding time of 1.5 min;

[0060] Step 7, subjecting the multi-principal alloy after recrystallization annealing to isothermal aging heat treatment, with the annealing temperature being 900° C. and the holding time being 0.5 h;

[0061] It should be noted that after the solid solution homogenization annealing treatment, the recrystallization annealing treatment and the isothermal aging heat treatment, the multi-principal alloy is cooled to room temperature by water quenching.

[0062] In order to determine the room temperature mechanical properties of the multi-principal alloy prepared in this comparative example, a room temperature quasi-static tensile test was performed on the multi-principal alloy prepared in this comparative example. The obtained tensile engineering stress-engineering strain curve is shown in FIG. Figure 4 As shown in the figure, it can be seen that the room temperature tensile yield strength of the multi-principal component alloy prepared in this comparative example is 1120MPa, the room temperature ultimate tensile strength is 1563MPa, and the elongation at break is only 17%. It can be obtained that compared with the multi-principal component alloy prepared in Example 1, the room temperature mechanical properties of the alloy in this comparative example have slightly improved strength but greatly reduced plasticity.

[0063] Comparative Example 2

[0064] Step 1: Grind and remove the surface oxide scale of Cr, Co, Ni, Al, and Ti metal raw materials, and the mass purity of the metal raw materials must be greater than or equal to 99.95%;

[0065] Step 2, weighing 28.6at% Cr, 28.7at% Co, 28.7at% Ni, 7at% Al, and 7at% Ti;

[0066] Step 3: Place the metal raw materials weighed in step 2 into a vacuum arc melting furnace for melting under a high-purity argon protection atmosphere; the melting current is maintained at 450A, electromagnetic stirring is added during the melting process, and the melting is repeated 5 times to obtain a multi-principal alloy original ingot (CrCoNi) 86 Al7Ti7;

[0067] Step 4: After smelting, a solid solution homogenization annealing treatment is performed at a temperature of 1200° C. and a holding time of 2 h. The multi-principal alloy is then cooled to room temperature by water quenching.

[0068] pass Figure 5 The SEM characterization results show that (CrCoNi) 86 Al7Ti7 precipitates a large amount of harmful Sigma phase at the grain boundaries, which causes grain boundary brittleness.

[0069] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A high-strength and high-plasticity L12 coherent nano-precipitation strengthened CrCoNi-based multi-principal alloy, characterized in that: The element composition of the high-strength and high-plasticity L12 coherent nano-precipitation strengthened CrCoNi-based multi-principal alloy is (CrCoNi) in atomic ratio. 90 Al5Ti5, in which Cr, Co and Ni are in equal atomic ratios; The high-strength and high-plasticity L12 coherent nano-precipitation strengthened CrCoNi-based multi-principal alloy contains a high-density L12 coherent nano-precipitation phase structure (Ni, Co) 3 (Al, Ti), and the preparation method thereof comprises: Step 1: By atomic ratio (CrCoNi) 90 Al5Ti5 Weigh the required amount of metal single substance raw materials and smelt them to obtain the original ingot of multi-principal alloy; Step 2: After smelting, the original ingot of the multi-principal alloy is subjected to solid solution homogenization annealing treatment at a temperature of 1100° C. and a holding time of 3 h; Step 3, rolling the multi-principal alloy after solid solution homogenization annealing treatment by a multi-pass cold rolling process, with a total thinning amount of 85%; Step 4, performing recrystallization annealing treatment on the rolled multi-principal alloy, the annealing temperature is 1100° C., and the holding time is 1.5 min; Step 5: subjecting the multi-principal alloy after recrystallization annealing to isothermal aging heat treatment, with the annealing temperature being 600° C. and the holding time being 2 h.

2. A method for preparing a high-strength and high-plasticity L12 coherent nano-precipitation strengthened CrCoNi-based multi-principal alloy, characterized in that: include: Step 1: By atomic ratio (CrCoNi) 90 Al5Ti5, wherein Cr, Co and Ni have equal atomic ratios, and the required amount of metal single substance raw materials are weighed and smelted to obtain a multi-principal alloy original ingot; Step 2: After smelting, the original ingot of the multi-principal alloy is subjected to solid solution homogenization annealing treatment at a temperature of 1100° C. and a holding time of 3 h; Step 3, rolling the multi-principal alloy after solid solution homogenization annealing treatment by a multi-pass cold rolling process, with a total thinning amount of 85%; Step 4, performing recrystallization annealing treatment on the rolled multi-principal alloy, the annealing temperature is 1100° C., and the holding time is 1.5 min; Step 5: subject the multi-principal component alloy after recrystallization annealing to isothermal aging heat treatment at an annealing temperature of 600°C and a holding time of 2 hours. The obtained high-strength and high-plasticity L12 coherent nano-precipitation strengthened CrCoNi-based multi-principal component alloy contains a high-density L12 coherent nano-precipitation phase structure (Ni, Co)3(Al, Ti).

3. The preparation method according to claim 2, characterized in that: In step 1, the purity of the metal element raw material by mass fraction is greater than or equal to 99.95%.

4. The preparation method according to claim 2, characterized in that: In step 1, the metal raw material is polished to remove surface oxide scale before smelting.

5. The preparation method according to claim 2, characterized in that: In step 1, the smelting specifically includes: placing the metal element raw material into a vacuum arc melting furnace for smelting under an argon protective atmosphere, wherein the smelting current is maintained at 400-500A, electromagnetic stirring is added during the smelting process, and the smelting is repeated 4-6 times.

6. The preparation method according to claim 2, characterized in that: After the solid solution homogenization annealing treatment, the recrystallization annealing treatment and the isothermal aging heat treatment, the multi-principal alloy is cooled to room temperature by water quenching.

Citation Information

Patent Citations

  • NiCoCr-containing medium / high-entropy alloy with non-equal atomic ratio and preparation method thereof

    CN112725678A

  • Preparation method of high-yield-strength CoCrNi-based medium-entropy alloy

    CN112853237A

  • 2.0 GPa-grade ultrahigh-yield-strength plastic CoCrNi-based medium-entropy alloy and preparation method thereof

    CN114086049A

  • L12 particle strongly-plasticized medium-entropy alloy and preparation method thereof

    CN114457270A

  • Coherent nanophase-reinforced medium-entropy alloy with excellent thermal stability and preparation method of coherent nanophase-reinforced medium-entropy alloy

    CN114807718A